The Mixed Effect of Role Overload on Extra-Role Performance: The Mediation Role of Behavioral Inhibition System/Behavioral Activation System Responses - Huang, Bo; Ma, Lina; Xia, Wei (Frontiers in Psychology, 2021)
The findings of existing studies of how role overload affects employees’ performance in organizations have been mixed and controversial. We draw on the hindrance–challenge framework to suggest that role overload contains both hindrance and challenge stressor components. We integrate this theory with the behavioral inhibition and behavioral activation systems (BIS and BAS) perspective to develop hypotheses about the effects of role overload on employees’ extra-role performance (voice). We suggest that although role overload is positively associated with withdrawal (a prototypical response of the BIS system) and ultimately negatively influences extra-role performance, it can also trigger job crafting (a prototypical response of the BAS system) and is, consequently, positively associated with extra-role performance. We further posit that the strength of these indirect effects is moderated by the quality of leader-member exchange (LMX). To support these hypotheses, we conducted a time-lagged study of 450 full-time preschool teachers from various Chinese kindergartens. As hypothesized, we found that withdrawal and job crafting mediated the relationship between role overload and extra-role performance. Further, LMX strengthens the positive relationship between role overload and job crafting. Taken together, our results suggest that role overload can be a mixed stressor that activates both negative and positive behaviors, thus ultimately having an impact on extra-role performance.